La distancia justa. Huellas y huecos de lo judío en Sergio Chejfec - Fiorani, Flavio (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The essay deals with two novels and a short story by Sergio Chejfec. Lenta biografía is an attempt to recreate the European past of the narrator’s father with its traumatic burden. In Mis dos mundos, Chejfec narrates the fade of the experience of walking in a park while at the same time evokes a family plot inhabited by features and traces of a fractured past. The short story El extranjero tells the spatial non-belonging as a place of origin and the Jewish heritage as exile. All texts are marked by uncertain space-time coordinates, mix fiction, autobiography and essay. They present errancy and excentricity as the most effective position to displace crystallized meanings of Jewish condition.